2013
DOI: 10.1590/1678-7757201302430
|View full text |Cite
|
Sign up to set email alerts
|

Catechin-incorporated dental copolymers inhibit growth of Streptococcus mutans

Abstract: Objective:To test the inhibitory growth activity of green tea catechin incorporated into dental resins compared to resins containing the broad-spectrum antimicrobial compound chlorhexidine against Streptococcus mutans in vitro.Material and Methods:The minimum inhibitory concentrations (MICs) of epigallocatechin-gallate (EGCg) and chlorhexidine (CHX) were determined according to the microdilution method. Resin discs (5 mm x 3 mm) were prepared from Bis-GMA/TEGDMA (R1) and Bis-GMA/CH3Bis-GMA (R2) comonomers (n=9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 34 publications
1
28
0
8
Order By: Relevance
“…CHX presents antimicrobial efficacy in vitro and in vivo (mouthwash) against salivary microbiota cariogenic and has a role in preventing the development of gingivitis [22]. Some studies compared EGCG with CHX [17,23,24,25,26]. e results of the comparison between CHX and EGCG showed that both substances were effective in inhibiting microbial the growth and biolm formation.…”
Section: Discussionmentioning
confidence: 99%
“…CHX presents antimicrobial efficacy in vitro and in vivo (mouthwash) against salivary microbiota cariogenic and has a role in preventing the development of gingivitis [22]. Some studies compared EGCG with CHX [17,23,24,25,26]. e results of the comparison between CHX and EGCG showed that both substances were effective in inhibiting microbial the growth and biolm formation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by previous studies and highlight the influence of polar, hydrophilic -OH groups on absorption. Sideridou et al 11) showed that poly-Bis-GMA presented higher water absorption than did poly-Bis-EMA and claimed that this was due to the higher cohesive energy density for hydrogen bonding of -OH (2,980 J/cm 3 ) when compared to the -O-group present in Bis-EMA (881 J/cm 3 ). Additionally, when analyzing three resin composites, Örtengren et al 27) showed that the absorption of composites with Bis-GMA and TEGDMA in their matrixes was comparatively higher than a composite with Bis-EMA, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…After every 24 h period, the discs were weighed (AUW 220, Shimadzu, Tokyo, Japan) until a constant mass (m 1) was attained, i.e., disc mass variation was less than ±0.01 mg in any 24 h period. The thickness and the diameter of the discs were measured using a digital caliper (MPI/E-101, Mitutoyo, Tokyo, Japan), and the volume (V ) was calculated in mm 3 . The discs were then individually placed in plastic vials and immersed in 20 mL of distilled water at 37±1ºC.…”
Section: Crosslink Density (Cld)mentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos mostram que essa substância desempenha efeito anticariogênico decorrente de sua efetiva ação antimicrobiana contra S. mutans e S. sobrinus (Sakanaka et al, 1989;Yoshino et al, 1996;Ferrazzano et al, 2011;Tamura et al, 2011;Xu et al, 2012;Shumi et al, 2014;Anita et al, 2015;Sarin et al, 2015), por impedir a aderência bacteriana ao dente por meio da inibição da enzima glicosiltransferase e da amilase bacteriana (Hamilton-Miller, 2001;Subramaniam et al, 2012;Jung et al, 2012;Cai et al, 2013). Devido à sua comprovada eficácia contra os micro-organismos e na inibição de metaloproteinases, esse extrato tem sido incorporado em materiais odontológicos, tais como, adesivos dentinários (Du et al, 2012), resinas compostas Mankovskaia et al, 2013) e cimentos de ionômero de vidro (Hu et al, 2013). Além disso, seu uso tem sido sugerido na redução da erosão e abrasão dentária (Magalhães et al, 2009;Kato et al, 2010), em solução para bochechos (Hirasawa et al, 2006;Jenabian et al, 2012;Neturi et al, 2014;Sarin et al, 2015), em dentifrícios (Maruyama et al, 2011;Hrishi et al, 2015) e como meio para a conservação de dentes avulsionados após traumatismos, mantendo a vitalidade das células do ligamento periodontal (Hwang et al, 2011;Jung et al, 2011;Poi et al, 2013;Ghasempour et al, 2015).…”
Section: Introductionunclassified